Inclusive Learning Adaptation Strategy: Analysis of Cognitive and Socio-Emotional Development in Students with Special Needs and Gifted Students in Secondary Schools - Ningsih, Mahdalena Prihatin; S, Neviyarni; Mudjiran, Mudjiran (Labor Program Studi Pendidikan Sosiologi, 2024)
This study aims to analyze inclusive learning adaptation strategies with a focus on the cognitive and social-emotional development of students with special needs and gifted students at the secondary school level. Using a qualitative approach with a literature study method, this study integrates findings from various literature sources published between 2018-2024, accessed through trusted academic databases. Data analysis uses a qualitative metasynthesis approach with validation through source triangulation and peer debriefing. The results of the study indicate that effective inclusive learning adaptation strategies require a holistic approach including: (1) individual needs-based learning differentiation, (2) comprehensive support systems, (3) collaboration of teaching teams and parental involvement, (4) assistive technology and curriculum modifications, and (5) ongoing professional development. These findings provide practical implications for the development of inclusive learning programs that accommodate the diversity of students' learning needs.